PELATIHAN PEMBUATAN KERUPUK BIJI BUAH NANGKA UNTUK MENINGKATKAN TARAF EKONOMI DI DESA CENGUNGKLUNG KECAMATAN GAYAM - Setyaningsih, Erwin; Fatimatuz Zahro, Diajeng; Nazah, Alfinatun; Sahri (JIK-PkM: Jurnal Inovatif dan Kreatif hasil Pengabdian kepada Masyarakat, 2024)
Improving economic standards in rural areas can be realized through the development of local potential and community empowerment. One of the potentials that can be utilized is the abundant jackfruit seeds in Cengungklung Village, Gayam District which are developed into crackers. Crackers are very suitable for snacks and complements the food menu, especially jackfruit seed crackers which are undoubtedly useful. Our program is to provide solutions for the community with training on jackfruit cracker crackers. Jackfruit seed crackers are a type of cracker that uses the basic ingredients of jackfruit seeds. These crackers can be consumed by all groups, both children, teenagers, and adults. The method used in this service uses ABCD (Asset Baset Community Development) by digging all assets owned by the village. The results of the service show that training in making jackfruit seed crackers can provide new knowledge and skills to the people of Cengungklung Village. By diversifying these products, it is hoped that people can increase their economic income. Market potential analysis shows a good opportunity to market these crackers at the local and regional levels. The implementation of this activity is expected to make a positive contribution to improving the economic level of the people of Cengungklung Village. In addition, product diversification can also have a positive impact on environmental sustainability and waste reduction, because jackfruit seeds that were previously considered waste can be used economically.